GRAMMATICAL METAPHOR IN BRUNO MARS’ SONGS - Joynet Tabita Niarta Manurung; Busmin Gurning (LINGUISTICA, 2014)
ABSTRACT This study deals with the types of ideational metaphor in Bruno Mars’ Songs. The objectives of this study are to find out the metaphorical codes applied in Bruno Mars’ songs and the reason of the writer to use metaphorical codes in the songs. The data are the song lyrics of Doo-Wops & Hooligans taken from internet. This research is conducted by using descriptive qualitative design to explain the grammatical metaphor coding. The finding shows that there are six types of ideational metaphor occur in the album, they are: material process, mental process, relational process, verbal process, behavioral process and existential process. The study shows that Material Process is the dominant which presented the action, activity, doing or happening to tell about Bruno Mars’ experiences.     Keywords: Grammatical Metaphor, Linguistics, Descriptive Qualitative Design